Lentiviral-mediated expression of cytochrome P450 2D6 in HepaRG cells: new means for in vitro xenobiotic biotransformation and cellular response to chimeric viral mRNA - Hugo Coppens-Exandier; Franz Mackanga; Thomas Darde; Corentin Bonhomme; Gaëlle Angenard; Patricia Leroyer; Catherine Ribault; Thomas Gicquel; Romain Pelletier; Flyuza Roshchina; Estelle Schaefer; Christophe Chesné; et al. (Archives of Toxicology, 2026)

Shifts in marine bird abundance and species composition following the 2014−2016 Pacific marine heatwave - Sarah A. Hoepfner; Anne L. Schaefer; Mary Anne Bishop (Frontiers in Marine Science, 2025)
The 2014−2016 Pacific marine heatwave (PMH) was an intense and prolonged environmental disturbance that significantly disrupted the marine food web, leading to widespread ecological impacts. The PMH contributed to major shifts in species distributions, mass mortalities, and reproductive failures among upper-trophic level species, including a massive die-off of common murres ( Uria aalge ) in the Gulf of Alaska (GOA). To assess the impact of the PMH on the winter marine bird community in Prince William Sound (PWS), a large embayment in the northern GOA, we analyzed changes in winter marine bird abundance and species composition in a series of bays before and after the PMH. The overall density of winter marine birds decreased and species composition significantly changed in PWS following the PMH. Specifically, common murres, cormorants, and loons decreased from pre-PMH survey densities, while marbled murrelet ( Brachyramphus marmoratus ) densities increased. The post-PMH increase in marbled murrelets, likely due to immigration, coincided with the rapid growth and spatial expansion in the PWS Pacific herring ( Clupea pallasii ) young-of-the-year population and with a smaller, 8-month marine heatwave across the northern GOA. We suggest the mass mortality and lack of recovery by the common murre population provided a competitive release enabling murrelets to exploit a growing forage fish population, and that murrelets may be more effective at shifting to warmer-water zooplankton during marine heatwave events. These results highlight the persistent upper-trophic level changes associated with the PMH and provide important insights into the ecological consequences of environmental disturbances. This is increasingly relevant given the predicted increase in frequency and intensity of marine heatwaves.

LandFrag : A Dataset to Investigate the Effects of Forest Loss and Fragmentation on Biodiversity - Thiago Gonçalves‐Souza; Maurício Humberto Vancine; Nathan J. Sanders; Nick M. Haddad; Lucas Cortinhas; Anne Lene T. O. Aase; Willian Moura de Aguiar; Marcelo Adrian Aizen; Víctor Arroyo‐Rodríguez; Arturo Baz; Maíra Benchimol; Enrico Bernard; et al. (Global Ecology and Biogeography, 2025)
Motivation The accelerated and widespread conversion of once continuous ecosystems into fragmented landscapes has driven ecological research to understand the response of biodiversity to local (fragment size) and landscape (forest cover and fragmentation) changes. This information has important theoretical and applied implications, but is still far from complete. We compiled the most comprehensive and updated database to investigate how these local and landscape changes determine species composition, abundance and trait diversity of multiple taxonomic groups in forest fragments across the globe. Main Types of Variables Contained We gathered data for 1472 forest fragments, providing information on the abundance and composition of 9154 species belonging to vertebrates, invertebrates, and plants. For 2703 of these species, we obtained more than 20 functional traits. We provided the spatial location and size of each fragment and metrics of landscape composition and configuration. Spatial Location and Grain The dataset includes 1472 forest fragments sampled in 121 studies from all continents except Antarctica. Most datasets (77%) are from tropical regions, 17% are from temperate regions, and 6% are from subtropical regions. Species abundance and composition were collected at the plot or fragment scale, whereas the landscape metrics were extracted with buffer size ranging from a radius of 200–2000 m. Time Period and Grain Data on the abundance of species and community composition were collected between 1994 and 2022, and the landscape metrics were extracted from the same year that a given study collected the abundance and composition data. Major Taxa and Level of Measurement The studied organisms included invertebrates (Arachnida, Insecta and Gastropoda; 41% of the datasets), vertebrates (Amphibia, Squamata, Aves and Mammalia; 44%), and vascular plants (19%), and the lowest level of identification was species or morphospecies. Software Format The dataset and code can be downloaded on Zenodo or GitHub.

Reclamation of an eroded lakeshore slope using small vegetation islands and terraces - Jim W. Schaefer; Amalesh Dhar; David S. Chanasyk; M. Anne Naeth (Ecological Engineering, 2024)

A single rapid heat stress episode does not result in prolonged elevations in salivary cortisol and C-reactive protein production in firefighters - Cory J. Coehoorn; Diana Cruz; Schaefer Mueller; Lilly Anne D. Kamberov; Jillian Danzy; Naina Bouchereau-Lal; Daniel Poole; Aaron Adams (Journal of Thermal Biology, 2024)

Light-level geolocation reveals the short-distance non-breeding movements and distribution of tufted puffins throughout the Northeast Pacific Ocean - Anne L. Schaefer; Kristen B. Gorman; Mary Anne Bishop (Frontiers in Marine Science, 2022)
Comprehensive assessments of cumulative impacts to seabirds have been hindered by an incomplete understanding of temporal and spatial patterns in marine habitat use, particularly during the non-breeding season when seabirds can range widely across the global ocean. Alcids are an important component of the meso-predator biodiversity of the North Pacific Ocean, yet the non-breeding movement ecology and distribution for many of the Pacific Auk species remain poorly quantified. Recent and projected declines for historically robust populations of tufted puffin ( Fratercula cirrhata ) in Alaska highlight the importance of resolving aspects of the species’ non-breeding ecology, especially the pelagic phenology and distribution. We used light-level geolocation to quantify the annual at-sea distribution of tufted puffins between a major Gulf of Alaska nesting colony (Middleton Island) and heretofore unknown migration routes and wintering areas. Geolocator data from 42 complete migration routes of reproductive adult tufted puffins collected primarily between 2018-2020 revealed that both males and females were short-distance migrants, wintering on average 616 km from their breeding colony. Tufted puffins departed the breeding grounds in early September. Males made fewer stops and arrived earlier to wintering areas than females, however the arrival date to the wintering area was later in 2019 compared to 2018. Males took 30.5 ± 16.7 (± standard deviation) days in 2018 and 30.8 ± 24.6 days in 2019 to arrive at wintering areas. Conversely, females took 36.1 ± 16.8 days in 2018 and 59.8 ± 17.3 days in 2019 to arrive at wintering areas. Adult tufted puffins wintered primarily in the deep offshore waters of the eastern Gulf of Alaska and partially in the adjacent Northeast Pacific Ocean over a period of 151.9 days ± 31.6 with spring migrations starting by late March. Males and females showed consistent spatial distributions within seasons, especially during winter. Tufted puffins shifted southwards throughout the non-breeding season, similar to other Atlantic and Northeast Pacific alcids. Our study provides important information on the at-sea non-breeding phenology and distribution of tufted puffins, which can inform risk assessments for the species including vulnerability to spatially and temporally explicit marine pollution, disease, fisheries by-catch, and ocean-climate variability.

MYT1L-associated neurodevelopmental disorder: description of 40 new cases and literature review of clinical and molecular aspects - Juliette Coursimault; Anne-Marie Guerrot; Michelle M. Morrow; Catherine Schramm; Francisca Millan Zamora; Anita Shanmugham; Shuxi Liu; Fanggeng Zou; Frédéric Bilan; Gwenaël Le Guyader; Ange-Line Bruel; Anne-Sophie Denommé-Pichon; et al. (Human Genetics, 2022)

Heatwave‐induced synchrony within forage fish portfolio disrupts energy flow to top pelagic predators - Mayumi L. Arimitsu; John F. Piatt; Scott Hatch; Robert M. Suryan; Sonia Batten; Mary Anne Bishop; Rob W. Campbell; Heather Coletti; Dan Cushing; Kristen Gorman; Russell R. Hopcroft; Kathy J. Kuletz; et al. (Global Change Biology, 2021)
During the Pacific marine heatwave of 2014–2016, abundance and quality of several key forage fish species in the Gulf of Alaska were simultaneously reduced throughout the system. Capelin ( Mallotus catervarius ), sand lance ( Ammodytes personatus ), and herring ( Clupea pallasii ) populations were at historically low levels, and within this community abrupt declines in portfolio effects identify trophic instability at the onset of the heatwave. Although compensatory changes in age structure, size, growth or energy content of forage fish were observed to varying degrees among all these forage fish, none were able to fully mitigate adverse impacts of the heatwave, which likely included both top‐down and bottom‐up forcing. Notably, changes to the demographic structure of forage fish suggested size‐selective removals typical of top‐down regulation. At the same time, changes in zooplankton communities may have driven bottom‐up regulation as copepod community structure shifted toward smaller, warm water species, and euphausiid biomass was reduced owing to the loss of cold‐water species. Mediated by these impacts on the forage fish community, an unprecedented disruption of the normal pelagic food web was signaled by higher trophic level disruptions during 2015–2016, when seabirds, marine mammals, and groundfish experienced shifts in distribution, mass mortalities, and reproductive failures. Unlike decadal‐scale variability underlying ecosystem regime shifts, the heatwave appeared to temporarily overwhelm the ability of the forage fish community to buffer against changes imposed by warm water anomalies, thereby eliminating any ecological advantages that may have accrued from having a suite of coexisting forage species with differing life‐history compensations.

Linear skin markings in common bottlenose dolphins ( Tursiops truncatus ) from the Indian River Lagoon, Florida - Elizabeth Murdoch Titcomb; Jessie Stevens; Anne Sleeman; Brandy Nelson; Luke Yrastorza; Adam M. Schaefer; Gregory D. Bossart; John S. Reif; Marilyn Mazzoil (Marine Mammal Science, 2020)
A previously undescribed skin abnormality, referred to as “linear skin markings” (LSM), has been identified in free‐ranging common bottlenose dolphins ( Tursiops truncatus ) in the Indian River Lagoon, Florida (IRL). The lesions were identified during photo‐identification surveys conducted from 2002 and 2015. LSM presented as distinct, parallel lines running dorso‐ventrally on the torso and varied in length and width. The goals of this study were to determine (1) prevalence of the condition in IRL dolphins, (2) age and sex distribution of affected animals, (3) spatial and temporal distribution patterns, (4) duration of the condition, and (5) development of hypotheses regarding the etiology of the condition. Among 1,357 individual dolphins identified during the study period, 96 (7.0%) showed evidence of LSM. Nearly all (98.8%) cases with an established home range occurred in the northern and central regions of the IRL. The majority of cases of known sex were female (85%), of which 100% had given birth to one or more calves. The mean age of animals with LSM when first observed was 7.3 with a range of 1–20 years. The maximum observed duration of LSM was 15 years. Once observed, the condition persisted indefinitely. The etiology of LSM has not been established.

Marine bird response to forage fish during winter in subarctic bays - Anne Louise Schaefer; Mary Anne Bishop; Richard Thorne (Fisheries Oceanography, 2020)
Despite the importance of understanding marine bird response to prey fish, few studies have examined this relationship during winter. Over a 5‐year period, we conducted synoptic marine bird and hydroacoustic forage fish surveys during early (November) and late (March) winter to characterize the factors influencing marine bird and forage fish dynamics at two spatial scales (fish school and bay) within subarctic bays of coastal Alaska, USA. Over 40% of observed marine birds were associated with a fish school (within 150 m of a fish school), although only 20% of fish schools were associated with birds. Seasonally, we recorded significantly more schools during early winter. The marine bird community also shifted from being comprised primarily of marbled murrelets ( Brachyramphus marmoratus ) and large gulls ( Larus spp.) in early winter to common murres ( Uria aalge ) in late winter. At the school level, marine birds were more likely to be associated with shallow fish schools within 500 m of shore and in smaller prey patches. At the bay level, gull abundance was positively associated with the total number of fish schools recorded, while diving birds were more abundant when fish schools were higher in the water column, in shallower bottom depths, and in areas with more eel grass habitat. Our results indicate the importance of temporal, habitat, and fish school variables as drivers of marine bird presence and abundance, underscoring the complexity of predator–prey dynamics in the marine environment during winter.

White Matter Integrity and Early Outcomes After Acute Ischemic Stroke - Mark R. Etherton; Ona Wu; Anne-Katrin Giese; Arne Lauer; Gregoire Boulouis; Brittany Mills; Lisa Cloonan; Kathleen L. Donahue; William Copen; Pamela Schaefer; Natalia S. Rost (Translational Stroke Research, 2019)

Deglaciation of coastal south‐western Spitsbergen dated with in situ cosmogenic 10 Be and 14 C measurements - Nicolás E. Young; Jennifer Lamp; Toby Koffman; Jason P. Briner; Joerg Schaefer; Endre F. Gjermundsen; Henriette Linge; Susan Zimmerman; Thomas P. Guilderson; Derek Fabel; Anne Hormes (Journal of Quaternary Science, 2018)
The Svalbard–Barents ice sheet was predominantly a marine‐based ice sheet and reconstructing the timing and rate of its decay during the last deglaciation informs predictions of future decay of marine‐based ice sheets (e.g. West Antarctica). Records of ice‐sheet change are routinely built with cosmogenic surface exposure ages, but in some regions, this method is complicated by the presence of isotopic inheritance yielding artificially old and erroneous exposure ages for the most recent deglaciation. We present 46 10 Be ages from south‐western Spitsbergen that, when paired with in situ 14 C measurements ( n = 5), constrain the timing of coastal deglaciation following the last glacial maximum. 10 Be and in situ 14 C measurements from bedrock along a ∼400‐m elevation transect reveal inheritance‐skewed 10 Be ages, whereas in situ 14 C measurements constrain 400 m of ice‐sheet thinning and coastal deglaciation at 17.4 ± 1.5 ka. Our in situ 14 C‐dated transect, combined with three additional 10 Be‐dated coastal sites, show that the south‐western margin of the Svalbard–Barents ice sheet retreated out of the Norwegian Sea between ∼18 and 16 ka. In situ 14 C measurements provide key chronological information on ice‐sheet response to the last termination in cases where measurements of long‐lived nuclides are compromised by isotopic inheritance.

Exposure to cox-2 inhibitors (coxibs) during the first trimester and pregnancy outcome: a prospective observational cohort study - Katarina Dathe; Stephanie Padberg; Stefanie Hultzsch; Luisa-Maria Köhler; Katja Meixner; Anne-Katrin Fietz; Tatjana Tissen-Diabaté; Reinhard Meister; Christof Schaefer (European Journal of Clinical Pharmacology, 2018)